Inovasi Media Pembelajaran Pendidikan Agama Islam Berbasis Artificial Intelligences Sebagai Media Pembelajaran Futuristik Di Era Metaverse - Eka Sukmawati; Khairani; Andi Fitriani Djollong; Mumu Muzayyin Maq; Khaerul (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
This study examines the potential use of Artificial Intelligence (AI) tools in improving the digital competence of Islamic Religious Education (PAI) teachers through a library research approach. Using systematic documentation techniques and content analysis, this study analyzes various literature, documents, and research results related to the implementation of AI in teacher professional development, especially in the context of Islamic education. Data were collected from reputable journals, reference books, and education policy documents in the period 2019-2024. The results of the analysis indicate that AI tools have significant potential in improving four aspects of PAI teachers' digital competence: digital literacy, learning content development, digital classroom management, and technology-based learning evaluation. The research findings also reveal challenges in implementing AI, such as the digital divide, resistance to change, and ethical considerations in the context of Islamic education. This study provides theoretical contributions to the development of an AI integration framework in improving the competence of PAI teachers, as well as providing practical implications for education policy makers and PAI practitioners in optimizing the use of AI technology for teacher professional development.